Perancangan Media Informasi Menggunakan Video Motion Graphic Wisata Pantai Gemah Kabupaten Tulungagung - Amzar Ghazidayana; Subari Subari; Saiful Yahya (MAVIS : Jurnal Desain Komunikasi Visual, 2021)
Gemah Beach is the one of old tourism objects that have been developed by the Government of Tulungagung Regency, with the development of the South Cross Line (SCL) to facilitate access people and tourists to visit Gemah Beach. There is no information on the tourist spots that are visualize in a media, it is unfortunate if with very supportive tourism potential and good infrastructure but not supported by effective and efficient information media. Therefore motion graphic video is one way to introduce Gemah beach to tourists. Obtained from visitor data, can be created motion graphic video design in accordance with the target audience of teenagers. Motion graphic video is video documentation and motion graphic that is combined into a single information media Gemah beach.